Time Course of Gene Expression during Porphyromonas gingivalis Strain ATCC 33277 Biofilm Formation - Yamamoto, Reiko (American Society for Microbiology, 2011)

(untitled)
Chronological gene expression patterns of biofilm-forming cells are important to understand bioactivity and pathogenicity of biofilms. For Porphyromonas gingivalis ATCC 33277 biofilm formation, the number of genes differentially regulated by more than 1.5-fold was highest during the growth stage (312/2,090 genes), and some pathogen-associated genes were time-dependently controlled.